Trabalhos experimentais de combate à "saúva limão" ou "saúva comum" Atta sexdens rubropilosa Forel, 1908 - Mariconi, Francisco A. M. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1963)
The purpose of the experiments described in this paper was to study the possibilities of eradicating hills of Atta sexdens rubropilosa Forel, 1908, which is the most important "saúva" ant (parasol ant) in the State of São Paulo, Brazil. The experiments were performed at Piracicaba, during the years 1960-1964. The following products were used in several projects: a) Nemagon (emulsifiable concentrate); b) aldrin (emulsifiable concentrate); c) "MM 33" (carbon bisulphide + methyl bromide); d) methyl bromide; e) carbon bisulphide; f) carbon bisulphide + phosphorus; g) aerosol of carbon bisulphide + heptachlor + chlordane; h) chlordane (emulsifiable concentrate); i) aldrin + fungicide (dust); j) dusts of heptachlor, chlordane, and aldrin, each plus a fungicide; and k) chlordane (dusts). The results obtained are seen in tables 1 to 13.